Fabrication of Feeding Plate in Neonates with Cleft Lip and Palate: Case Series - Dallakoti, Parayash; Rai, Amita; Sundas, Sunanda; Koirala, Bandana; Dali, Mamta; Dhakal, Neha (Birat Journal of Health Sciences, 2022)
Cleft lip and palate (CLP) is a common craniofacial anomaly which can be syndromic or non-syndromic. In children with CLP, feeding is the biggest concern due to lack of oral seal owing to the presence of clefts in the oral cavity. To achieve a near normal feeding, feeding plates are delivered to restore the separation thus helping to create negative intraoral pressure during suckling. Impression making for the fabrication of feeding plate is incredibly challenging procedure but selection of appropriate impression material, patient positioning during impression making and preparation for management of emergency mishaps can make the procedure easier and safer. Present case series highlights the fabrication and delivery of feeding plates made up of two different materials (Ethylene vinyl acetate and self-cure acrylic resin) in three neonates who were four, fourteen and five days old.